Hybrid machining of structural ceramics - Choon, Yee King. (2010)
Experimental studies on the laser etching of SiC structural ceramics etched by 355nm-10 AVIA UV laser in several environments including air, water, KOH, methanol, ethanol and IPA (isopropanol) were conducted. Two methodologies of liquid-assisted laser etching were adopted: (1) static 1.6cm-thick of water and KOH, (2) alcohol thin-film with thickness less than 1mm respectively. It was found that texture etched in all liquid was free of debris and low or absence in oxygen content. For alcohol-thin-film-assisted etching, a 10 fold increase in material removal rate compared to water and KOH is observed, with depth of texture ranged from 100 to 330 µm. Explosive melt expulsion could be the dominant material removal mechanism, which enhanced the etching efficiency in water and KOH according to the observed cavities on the etched surface. For alcohol-assisted laser etching, it is conceivable that the fast quenching ability of alcohol owing to its high volatility and low viscous flow was beneficial for material ejection and minimizing redeposition of material. Based on the result, methanol was concluded to be the most effective candidate that could achieve high MRR with compromising the surface quality.